Menghitung Waktu Panen Tanaman Bawang Merah Berbasis Heat Unit pada Pemberian Pupuk Organik di Tanah Gambut - Djoko Eko Hadi Susilo (Anterior Jurnal, 2016)
Determining of the harvest of onion in the peat soil can be done by using physiological harvest criteria, but calculating the appropriate of harvest time can support the quality of harvesting of the onion plant. This study was conducted by using polybags in research and experiment gardens of the Faculty of Agriculture and Forestry of the University of Muhammadiyah Palangkaraya from April to June in 2016. The given fertilization was an organic fertilizer in peat soil by using stall fertilizer like chicken feces with dosages of 15-30 tons ha-1 (PK) and bokashi of stall fertilizer of chicken feces with a dosage of 2-5 tons ha-1 (BK). The observation was done to the calculation of daily temperature (°C), the average of daily temperature (°C), and the unit of heat (heat unit) (°C day) as long as the cultivation of onion plant. The results showed that the harvest time that appropriate to the harvest physiological criteria in the treatment of BK at the age of 57 days after planting is relatively accurate and appropriate because it has a heating unit for 947,17oC day, and the harvest time that appropriate to the harvest physiological criteria of PK treatment at the age of 59 days after planting is relatively late because it has a heating unit for 978,09oC day.